Understanding the Civil-Military Relations in Pakistan: A Case Study of the PML-N Regime (2013-18) - Ali, Sharaf (Annals of Human and Social Sciences, 2024)
This Paper aimed to re-assess the changing dynamics of the Civil-Military relations during the period of the PML-N regime (2013-18). This Paper provided a review of the significant developments in the Civil-Military relations during the aforesaid period. This study has mainly relied on the descriptive and case study research methods i.e. for achieving the objectives of this research. The results of the study provided that the Civilian leadership of the PML-N regime simply failed to gain any extra roam for changing the traditional dynamics of the civil-military relations i.e. in favor of the democratically elected civilian leadership. Rather, the PML-N regime directly involved the military for overcoming the politico-economic and governance issues which obviously lead to sustain the traditional stronghold of the military i.e. in the politics of Pakistan. This study recommended that the political leadership shall have to change their own mindset first, and later, they have to devise a serious plan/strategy to bring the pre-requisite changes in the internal structure of the political parties i.e. for strengthening the base of democracy which serves as the actual source of strength for the civilian leadership. Additionally, for the purpose of gaining/enhancing the base of their legitimate power, the civilian leadership needs to focus on improving the overall quality of the governance as well.